2020
DOI: 10.13171/mjc10402004201366aa
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and analysis of heavy metals of Nerium oleander (L.) leaves

Abstract: <p>The main objective of this research is studying phytochemical screening of the extracts of polluted <em>Nerium oleander</em> (L.), and unpolluted<em> Nerium oleander</em> (L.) collected from Meknes region (Morocco), and determination of metals concentration that can have harmful effects on human health. In addition, the study provides scientific data.</p><p>Studies have shown that the two extracts of polluted <em>Nerium oleander</em> (L.) and unpolluted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The concentration of MTE accumulated by Nerium oleander in Setif Province, Nigeria shows the rank in concentration of the elements Mn> Sb> Bi> Pb> Fe> Cu> Cd. Other studies on the concentration of MTE in the leaves of N. oleander have revealed similar results (Espinosa and Oliva 2006;Mingorance and Oliva 2006;Mingorance et al 2007;Santos et al 2019;Fliou et al 2020;Ibrahim and El Afandi 2020a).…”
Section: Discussionsupporting
confidence: 74%
“…The concentration of MTE accumulated by Nerium oleander in Setif Province, Nigeria shows the rank in concentration of the elements Mn> Sb> Bi> Pb> Fe> Cu> Cd. Other studies on the concentration of MTE in the leaves of N. oleander have revealed similar results (Espinosa and Oliva 2006;Mingorance and Oliva 2006;Mingorance et al 2007;Santos et al 2019;Fliou et al 2020;Ibrahim and El Afandi 2020a).…”
Section: Discussionsupporting
confidence: 74%
“…Samples taken from polluted sites had significantly higher percentage values than those from garden sites. Results demonstrate that P. oleracea L. may grow in wastelands subjected to fertilizer, water, traffic, and air stress, while simultaneously exhibiting reasonably high phytoconstituent levels under these conditions [13]. Examining the effects of different levels of exposure to road dust on the phytochemical composition of a sample of the traditional African plant Barleria dinteri L. In the locations samples of B. dinteri L. were taken from two different locations one next to a dusty road the test sample and another further away the control sample.…”
Section: Introductionmentioning
confidence: 93%
“…Nowadays, traffic air pollution, dust, or Particulate Matter (PM), is one of the primary issues affecting human health and crops, owing mostly to the rapid development of industrial activity and road traffic [11]. Research has indicated that there are differences in the total flavonoid content between the two extracts obtained from the polluted and unpolluted N. oleander L. plants [12].…”
Section: Review Of Literaturementioning
confidence: 99%